Cetirizine and Dexamethasone in Sepsis: Insights into Maresin-1 Signaling and Cytokine Regulation - Aydin, Yalcin; Borku, Mehmet Kazim; Ugur, Kader; Eroksuz, Yesari; Emre, Elif; Incili, Canan Akdeniz; Lee, Do-Youn (Mdpi, 2025)
Background/Objectives: Sepsis remains one of the leading causes of mortality, yet its etiopathogenesis is still not fully understood. This study aimed to investigate the effects of cetirizine and dexamethasone (alone and in combination) on serum levels of Maresin-1 (MaR-1), TNF-alpha, IFN-gamma, IL-1, IL-2, IL-6, IL-8, and IL-10 in a rat model of sepsis induced by the cecal ligation and puncture (CLP) method. Methods: Male Sprague Dawley rats aged 8-10 weeks were used and randomly divided into 7 groups, each containing 7 rats: Group 1 (Control), Group 2 (Sham), Group 3 (Sepsis), Group 4 (Sepsis + Saline), Group 5 (Sepsis + Cetirizine), Group 6 (Sepsis + Dexamethasone), and Group 7 (Sepsis + Cetirizine + Dexamethasone). Sepsis was induced via CLP in all groups except Control and Sham. Results: In the sepsis groups (G3-G7), neutrophil and white blood cell counts increased while lymphocyte counts decreased (p < 0.05). In groups treated with cetirizine and/or dexamethasone (G5-G7), a significant decrease in neutrophils and an increase in lymphocytes were observed. MaR-1 levels significantly decreased (p < 0.05) in all sepsis-induced groups compared to controls, while interleukin levels significantly increased. Cetirizine and dexamethasone supplementation significantly increased MaR-1 levels and decreased interleukin levels (p < 0.05). The combined treatment was more effective. Conclusions: This study is the first to highlight the potential of MaR-1 as a critical biomarker in sepsis diagnosis and monitoring, and cetirizine and dexamethasone, especially in combination, may represent a promising therapeutic option in sepsis management.
Keywords: sepsis; dexamethasone; cetirizine; Maresin-1; interleukins